Jun NH(2)-terminal kinase (JNK) prevents nuclear β-catenin accumulation and regulates axis formation in Xenopus embryos - Liao, Guanghong (National Academy of Sciences, 2006)
Jun NH(2)-terminal kinases (JNKs) regulate convergent extension movements in Xenopus embryos through the noncanonical Wnt/planar cell polarity pathway. In addition, there is a high level of maternal JNK activity spanning from oocyte maturation until the onset of gastrulation that has no defined functions. Here, we show that maternal JNK activation requires Dishevelled and JNK is enriched in the nucleus of Xenopus embryos. Although JNK activity is not required for the glycogen synthase kinase-3-mediated degradation of β-catenin, inhibition of the maternal JNK signaling by morpholino-antisense oligos causes hyperdorsalization of Xenopus embryos and ectopic expression of the Wnt/β-catenin target genes. These effects are associated with an increased level of nuclear and nonmembrane-bound β-catenin. Moreover, ventral injection of the constitutive-active Jnk mRNA blocks β-catenin-induced axis duplication, and dorsal injection of active Jnk mRNA into Xenopus embryos decreases the dorsal marker gene expression. In mammalian cells, activation of JNK signaling reduces Wnt3A-induced and β-catenin-mediated gene expression. Furthermore, activation of JNK signaling rapidly induces the nuclear export of β-catenin. Taken together, these results suggest that JNK antagonizes the canonical Wnt pathway by regulating the nucleocytoplasmic transport of β-catenin rather than its cytoplasmic stability. Thus, the high level of sustained maternal JNK activity in early Xenopus embryos may provide a timing mechanism for controlling the dorsal axis formation.